The use of analogue sites for native ecosystem mine rehabilitation—a case study incorporating effective approaches for selection, monitoring and analysis - Spain, CS; Jones, JL; Nuske, SJ; Robinson, D (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
Evaluating the success of any native ecosystem rehabilitation requires its careful comparison to a desired target. In mine rehabilitation, these targets are often native vegetation communities that were present pre-mining or in the surrounding landscape. Field monitoring plots representative of these community targets are known as analogue or reference sites and are widely used in rehabilitation efforts, yet there is a dearth of literature available on their effective use in mining contexts. Using Whitehaven Coal’s rehabilitation operations as a case study, we explore considerations for effective analogue site selection, monitoring and data analysis in the context of native ecosystem mine rehabilitation. To identify the most appropriate targets for the existing or desired mature rehabilitation at Whitehaven operations, an evaluative comparison of landform pattern, location, floristic and structural similarity between the rehabilitation areas and native vegetation communities was conducted. After accounting for operation-specific mine rehabilitation objectives, the best matching candidate communities, based on landscape and rehabilitation context, were selected as final targets. Spatially replicated analogue sites, representing the best-on-offer examples of the targeted ecological community, were established and subjected to an ongoing monitoring program focused on appropriate characterisation of the communities, given temporal and spatial variations in species cover and detectability that occur in the targeted woodland ecosystems. This variability is captured through multiyear resampling of a subset of analogue sites, thereby efficiently providing quantitative data on climatic responses to community composition. The resultant multi-year ‘library’ of analogue site data allows calculation of analogue benchmark values that can be adapted to provide evolving, dynamic benchmarks, for example, by using the most appropriate subset of current and historical data reflective of contemporary climatic conditions. Methods to calculate these benchmarks encompass averaging replicated site data across climatically similar years but may be extended to complex techniques such as ordination or hierarchical Bayesian modelling. Overall, methods to enhance mine rehabilitation success are urgently required, and to help achieve this goal, we provide a process framework for the use of analogue sites in mine rehabilitation.
Keywords: mine rehabilitation